2014
DOI: 10.1016/j.tsf.2014.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Durability of thermochromic VO2 thin films under heating and humidity: Effect of Al oxide top coatings

Abstract: An explorative study was performed on sputter-deposited thermochromic (TC) VO 2 films exposed to heat treatment under dry and humid conditions. The ambient conditions were harsh and 80-nm-thick VO 2 films rapidly converted to non-TC V 2 O 5 . It was found that a 30-nm-thick sputter-deposited Al oxide top coating provided good protection and delayed the oxidation for more than one day upon heating in dry air at 300 °C and that protection occurred for several days at 95 % relative humidity and 60 °C. The thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Chen et al [199] later reported higher T lum of 61.5.%. The durability of the VO 2 films has also been improved by the addition of an Al 2 O 3 over layer which was shown to provide protection against heat (300 • C for one day) and relative humidity of 95% [200].…”
Section: Improving the Aesthetics Of Thermochromic Filmsmentioning
confidence: 99%
“…Chen et al [199] later reported higher T lum of 61.5.%. The durability of the VO 2 films has also been improved by the addition of an Al 2 O 3 over layer which was shown to provide protection against heat (300 • C for one day) and relative humidity of 95% [200].…”
Section: Improving the Aesthetics Of Thermochromic Filmsmentioning
confidence: 99%
“…The durability of VO2 is also dependent on the deposition technique and is improved for films with high density and large grain size [66,108]. Figure 15 depicts T(λ) for similar VO2 films over-coated with 10 nm and 30 nm of sputter deposited alumina and heat treated at 300 °C for periods in the range 1 < th < 30 h [105]. Clearly the top layer provides good protection, and only the thinnest Al2O3 layer and the longest heat-treatment period yielded some minor decline of the thermochromism.…”
Section: Towards Vo2-based Thin Films For Glazingsmentioning
confidence: 99%
“…Chemically stable oxide films such as Al 2 O 3 [54,85], CeO 2 [86,87], WO 3 [64], etc., have been studied to keep VO 2 away from oxidant like water and O 2 in air. It should be noted that the selected materials to be used as protective layers might affect the optical properties of VO 2 , where dual enhancement in the optical properties and the stability is preferred.…”
Section: Protective Layers For Vo 2 Filmsmentioning
confidence: 99%
“…Al oxide is a typical material that has been investigated as a protection layer for VO 2 coatings. In work reported by Ji et al [54], different thicknesses of Al oxide protective layers have been deposited for VO 2 by DC magnetron sputtering. The durability of the samples was evaluated at a high temperature around 300°C in dry air and highly humid environment.…”
Section: Protective Layers For Vo 2 Filmsmentioning
confidence: 99%
See 1 more Smart Citation